PERKEMBANGAN FUNGSI DAN FISIK BANGUNAN DI AREA BEKAS BENTENG KRATON YOGYAKARTA - , Ani Hastuti Arthasar ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Fort that encloses the Palace area since the beginning of construction has a defensive function and symbolic. With the beginning of the collapse of the fort, it became lost the defensive function as building defenses, although the symbolic function can still be perceived ascircumsribe the Palace area. The collapse of the fort makes any space in the former fortress which later developed into a series of residential buildings. By using inductive qualitative methodology, this study was conducted to determine how the process of development and function of the physical building in the fort area of the former sultan's palace, why these developments occurred, and the factors that influence. The development of function that occurs is closely related to economic development, where its influence is greater than the influence of culture. While physical development can be classified into the three-way development and nine types of development. Several factors affect the development of physical function and are classified into two, namely (1) interms of the direction and type of building development, and (2) of the local aspects of culture.